The Effect of Wattpad Application Use on Students’ Reading Behavior in the Library and Information Science Study Program at Universitas Negeri Padang - Melati Aulia; Nurizzati (Darul Yasin Al Sys, 2026)
Digital technology has transformed students’ reading practices by shifting engagement from printed materials toward digital media. Wattpad provides access to diverse digital texts, predominantly fiction and user-generated content; however, its relationship with university students’ reading behavior requires further examination. This study aimed to analyze the effect of Wattpad use on the reading behavior of students in the Library and Information Science Study Program at Universitas Negeri Padang. A quantitative descriptive approach was employed. The study population comprised 250 students, from whom a sample of 71 respondents was determined using the Slovin formula. Data were collected through a Likert-scale questionnaire and analyzed using descriptive statistics and simple linear regression with SPSS. The findings indicate that both Wattpad use and students’ reading behavior were categorized as good. Wattpad use had a positive and statistically significant effect on reading behavior, explaining 36.3% of its variance (R² = .363). These findings demonstrate that engagement with Wattpad contributes meaningfully to students’ reading behavior. The study highlights the potential of Wattpad as a complementary digital reading medium for promoting reading engagement and strengthening digital literacy initiatives in higher education.